2018
DOI: 10.1021/acs.jpcc.8b04281
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of p-Type Cu2O, CuO, and NiO from Hybrid Density Functional Theory

Abstract: The electronic transport coefficients of three Earth-abundant metal oxides Cu2O, CuO, and NiO were investigated using hybrid density functional theory (DFT). Hybrid DFT methods combined with local Gaussian-type basis sets enabled band structure studies on both non-magnetic and magnetic p-type metal oxides without empirical corrections. The CRYSTAL code was used for obtaining the wavefunction, and the transport properties were calculated with two different methodologies to benchmark their accuracy: a numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 78 publications
4
36
0
Order By: Relevance
“…So far, good oxide TE materials are p-type conduction NaCo2O4, NaxCoO2 and Ca3Co4O9+δ and n-type conduction SrTiO3, CaMnO3 and ZnO 9 . In this context, significantly large value of S in ptype cuprous oxide Cu2O with direct band gap (~ 2.17 eV) 10 and melting point ~1508 K has been reported in experimentally 11,12,13,14,15 and theoretically 16,17 . For instance, Young et al 11 reported S around 1050 µV/K at 500 K for single crystalline Cu2O.…”
Section: Introductionmentioning
confidence: 90%
“…So far, good oxide TE materials are p-type conduction NaCo2O4, NaxCoO2 and Ca3Co4O9+δ and n-type conduction SrTiO3, CaMnO3 and ZnO 9 . In this context, significantly large value of S in ptype cuprous oxide Cu2O with direct band gap (~ 2.17 eV) 10 and melting point ~1508 K has been reported in experimentally 11,12,13,14,15 and theoretically 16,17 . For instance, Young et al 11 reported S around 1050 µV/K at 500 K for single crystalline Cu2O.…”
Section: Introductionmentioning
confidence: 90%
“…It is important to remark, as depicted in Figure 1 , that the final layer of the stack is an aluminum layer. The electrical resistivity of bulk CuO (≈2.5 m [ 24 ]) is several orders of magnitude higher than the bulk resistivity of Al (2.650 × 10 −8 m [ 25 ]). Hence, it can safely be assumed that the electrical resistivity of the multilayer is defined by the film properties of Al because the resistivity of the multilayer can be approximated by a parallel circuit model [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been shown that the electronic properties and the geometry of NiO are reliably described with hybrid DFT methods even though the band gap is overestimated. 14 , 71 For comparison, GGA-PBE functional severely underestimates the band gap of NiO, predicting a value of only 0.5 eV. 21 An interesting possibility for further improvement is the utilization of self-consistent hybrids, as implemented in CRYSTAL, in which case the amount of exact exchange is self-consistently obtained for different types of materials.…”
Section: Resultsmentioning
confidence: 99%
“…Transition-metal oxides play a crucial role in a wide range of applications from catalysis to electronics. 8 14 It is well known that standard generalized gradient approximation (GGA) functionals such as Perdew–Burke–Ernzerhof (PBE) fail to correctly treat the magnetic moments and electronic structure of systems such as strongly correlated transition-metal oxides, sometimes even favoring a wrong magnetic ground state. 15 22 Even in the case of nonmagnetic transition-metal oxides such as Cu 2 O, the band structure may not be correctly described by GGA functionals.…”
Section: Introductionmentioning
confidence: 99%